The Role of Job Satisfaction in Mediating the Influence of Organizational Culture and Leadership on Employee Performance (Study at PT. Arta Boga Cemerlang Gianyar Branch) - PUTRA, I Gusti Ngurah Raditya; SARA, I Made; SITIARI, Ni Wayan (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to determine the role of job satisfaction in mediating the influence of organizational culture and leadership on employee performance. The object of this research is PT. Arta Cemerlang Catering Gianyar Branch. The population of this study includes all employees in 2023, totaling 32 employees. The sample method was determined using census techniques, so the sample for this study was 32 respondents. The data collection method is a survey with a questionnaire. The analysis technique used is descriptive analysis and inferential analysis with Partial Least Square (PLS). The research results show that: (1) organizational culture has a positive and significant effect on job satisfaction, (2) work culture has a positive and significant effect on employee performance, (3) leadership has a positive and significant effect on job satisfaction, (4) leadership has a positive but significant effect on job satisfaction. not significant on employee performance, (5) job satisfaction has a positive and significant effect on employee performance, (6) job satisfaction is able to mediate the relationship between organizational culture and employee performance, (7) job satisfaction is able to mediate leadership on employee performance.